Photocatalytic membranes: a new perspective for persistent organic pollutants removal - Kanakaraju, Devagi; Pei Sean, Goh; Mahesan Naidu, Subramaniam; Jun Wei, Lim; Woei Jye, Lau; Ahmad Fauzi, Ismail (Springer, 2021)
The presence of conventional and emerging pollutants infiltrating into our water bodies is a course of concern as they have seriously threatened water security. Established techniques such as photocatalysis and membrane technology have proven to be promising in removing various persistent organic pollutants (POP) from wastewaters. The emergence of hybrid photocatalytic membrane which incorporates both photocatalysis and membrane technology has shown greater potential in treating POP laden wastewater based on their synergistic effects. This article provides an in-depth review on the roles of both photocatalysis and membrane technology in hybrid photocatalytic membranes for the treatment of POP containing wastewaters. A concise introduction on POP’s in terms of examples, their origins and their effect on a multitude of organisms are critically reviewed. The fundamentals of photocatalytic mechanism, current directions in photocatalyst design and their employment to treat POP’s are also discussed. Finally, the challenges and future direction in this field are presented.